Construção social da realidade no ensino e na pesquisa em estratégia dos mestrados profissionais em administração sob a ótica dos docentes - Carvalho, Leonardo de (2017)
The purpose of this study is to understand how teaching and research in strategy is constituted in professional masters in administration from the perspective of teachers. For this, the body of knowledge in strategy, teaching and research methods and techniques, as well as the pedagogical schools used by teachers, from the perspective of Sociology of Knowledge, are used in the social construction of the reality of the field. The research is qualitative, using the multiple case study method, through the application of semistructured interviews with the strategy teachers of the 28 professional master's programs in management that have in their curriculum the discipline of strategy. In addition, a data triangulation was developed with lattes curricula of research subjects, menus and teaching plans. It was possible to understand that as regards the body of knowledge used by the teachers / researchers, the same one approaches the main authors of the field of the strategy, but it includes different authors related to the field of research, knowledge and academic formation of the teachers. Among the most used teaching techniques are the case method, the expository and dialogic classes, the debates and discussions and the seminars, being the written evaluations, individual and group work and the composition of articles the main evaluation methodologies. The main research methodologies were the qualitative ones, however, a direct relation with the research objectives was perceived, causing an alternation between the qualitative and quantitative methodologies. The most frequent methods of data collection were interviews, documents and surveys. The most used methods of analysis were content and speech analysis and statistical analysis with the use of software. Regarding the social role of the interviewees, it was possible to understand that it is not restricted to teaching and research, but it is related to other roles such as coordination, administrative, evaluator, editor, consultant and others. It was relevant the relationship between theory and practice presented by the interviewees, a relationship that permeated from the selection of students to the final product of research developed by students in professional masters. Finally, in the developed diagnosis it was possible to understand that the dissemination of the research data can contribute to the advances in the field of strategy in the professional masters in administration.